DIGITAL HEALTH TECHNOLOGIES FOR ANTI-CORRUPTION, TRANSPARENCY AND ACCOUNTABILITY: OPPORTUNITIES AND CHALLENGES FOR ZIMBABWE - Chilunjika, Sharon; Chilunjika, Alouis (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This paper explores the opportunities of digital health technologies as platforms that can be adopted to foster transparency, accountability and anti-corruption measures in Zimbabwe’s public health sector. Corruption in the health domain has severe consequences for quality, access, equity and efficiency of health services, and is a barrier to the attainment of Universal Health Coverage. Digital health technologies that can foster accountability, transparency, detect and prevent corruption are particularly crucial to developing countries were corruption is a huge threat. This paper, being qualitative in its approach relied on an extensive review of scholarly journals, trusted databases, websites, policy documents and newspapers that shed light on digital health technologies and their impact on corruption. The paper establishes that Zimbabwe’s public health sector is highly susceptible to corruption due to system complexity, large sums of resources involved, information asymmetry and the nature of the pharmaceutical supply chain. The study found out that digital health technologies can support anti-corruption by impacting citizen scrutiny in a number of ways including reporting on corruption, facilitating citizen participation and promoting accountability and transparency. The technologies reviewed are transparency portals, artificial intelligence, decentralized digital ledgers, and whistleblowing tools. Nevertheless, the study established that these technologies can also usher novel corruption opportunities in the health domain through the dark web and cryptocurrencies. The study concludes with some considerations for policy makers on how technologies can be harnessed to ensure that their benefits are reaped.